Dermatoglyphics A Good Tool In Preventive Medicine - Mollik, MJH; Habib, MA (Journal of Armed Forces Medical College, Bangladesh, 2012)
DOI: http://dx.doi.org/10.3329/jafmc.v7i2.10374 JAFMC 2011; 7(2): 1-2